Bilateral Contralaterally Controlled Functional Electrical Stimulation Reveals New Insights Into the Interhemispheric Competition Model in Chronic Stroke. (September 2019) - Cunningham, David A.; Knutson, Jayme S.; Sankarasubramanian, Vishwanath; Potter-Baker, Kelsey A.; Machado, Andre G.; Plow, Ela B.
Background. Upper-limb chronic stroke hemiplegia was once thought to persist because of disproportionate amounts of inhibition imposed from the contralesional on the ipsilesional hemisphere. Thus, one rehabilitation strategy involves discouraging engagement of the contralesional hemisphere by only engaging the impaired upper limb with intensive unilateral activities. However, this premise has recently been debated and has been shown to be task specific and/or apply only to a subset of the stroke population. Bilateral rehabilitation, conversely, engages both hemispheres and has been shown to benefit motor recovery. To determine what neurophysiological strategies bilateral therapies may engage, we compared the effects of a bilateral and unilateral based therapy using transcranial magnetic stimulation. Methods. We adopted a peripheral electrical stimulation paradigm where participants received 1 session of bilateral contralaterally controlled functional electrical stimulation (CCFES) and 1 session of unilateral cyclic neuromuscular electrical stimulation (cNMES) in a repeated-measures design. In all, 15 chronic stroke participants with a wide range of motor impairments (upper extremity Fugl-Meyer score: 15 [severe] to 63 [mild]) underwent single 1-hour sessions of CCFES and cNMES. We measured whether CCFES and cNMES produced different effects on interhemispheric inhibition (IHI) to the ipsilesional hemisphere, ipsilesional corticospinal output, and ipsilateral corticospinal output originating from the contralesional hemisphere. Results. CCFES reduced IHI and maintained ipsilesional output when compared with cNMES. We found no effect on ipsilateral output for either condition. Finally, the less-impaired participants demonstrated a greater increase in ipsilesional output following CCFES. Conclusions. Our results suggest that bilateral therapies are capable of alleviating inhibition on the ipsilesional hemisphere and enhancing output to the paretic limb.